Do Not Resuscitate: The Fight to Revive Inquest Proceedings in the United States - Maryl Evans (Washington University Journal of Law & Policy, 2021)
When a suspicious death occurs in some states, coroners, medical examiners, or other officials conduct an inquest proceeding to investigate. Part I of this Note traces the roots of inquest proceedings and examines adaptations that have been made by different jurisdictions. Part II analyzes how jurisdictions balance the decedent’s family’s interest in justice and closure with the accused’s constitutional rights and fairness. Part III proposes a hybrid restructuring of inquest proceedings to ensure due process and further the fact-finding principles of an inquisitorial system to benefit all parties. Evans argues states should adopt inquest proceedings that balance the interests of the decedent's family, the accused, and the wider community rather than emulating the adversarial trial-like proceedings of traditional criminal litigation.
Keywords: inquest; inquest proceeding; inquest proceedings; coroner; coroners; medical examiner; medical examiners; decedent; decedents; evidence; fact finding; trial; trial proceeding; trial proceedings; death; due process